Under-pricing of IPOs in Indian capital market and determinants of Under-pricing - Middi, Appala Raju (Archives of Business Research, 2017)
Organisations in their endeavour to expand diversify and to meet other strategic investment initiatives aim at IPOs (equity) as important source finance. Organisations approach Investment Bankers for pricing the issue which is expected to be well taken by the prospective investors in the market. Equity valuation given by investment bankers very often tend to be overestimated. The equity after the issue tend to be under-priced as the price fixed by the investment bankers is not based on true fundamentals and intrinsic value of the business, but on the inflated values of the company. Irrational investors, keeping the base on the valuations given by the investment bankers tend to lose the value of their investments